Animal, but not human, faces engage the distributed face network in adolescents with autism. Issue 2 (14th April 2015) - Whyte, Elisabeth M.; Behrmann, Marlene; Minshew, Nancy J.; Garcia, Natalie V.; Scherf, K. Suzanne
Abstract: Multiple hypotheses have been offered to explain the impaired face‐processing behavior and the accompanying underlying disruptions in neural circuitry among individuals with autism. We explored the specificity of atypical face‐processing activation and potential alterations to fusiform gyrus (FG) morphology as potential underlying mechanisms. Adolescents with high functioning autism (HFA) and age‐matched typically developing (TD) adolescents were scanned with sMRI and fMRI as they observed human and animal faces. In spite of exhibiting comparable face recognition behavior, the HFA adolescents evinced hypo‐activation throughout the face‐processing system in response to unfamiliar human, but not animal, faces. They also exhibited greater activation in affective regions of the face‐processing network in response to animal, but not human, faces. Importantly, this atypical pattern of activation in response to human faces was not related to atypical structural properties of the FG. This atypical neural response to human faces in autism may stem from abnormalities in the ability to represent the reward value of social (i.e. conspecific) stimuli. Abstract : High functioning adolescents (HFA) with autism and age‐matched typically developing (TD) adolescents completed MRI scans as they observed human and animal faces. Compared to TD adolescents, HFA adolescents exhibited hypo‐activation in the face‐processing system only to human, but not animal, faces. This atypical neural response to human faces in autism may stem from abnormalities in the ability to represent the reward value of social (i.e. conspecific) stimuli.